Comparison of TOPSIS and SAW Methods for The Determination of The Best Employees at Insan Permata Hospital - Sumanto Sumanto (J I M P - Jurnal Informatika Merdeka Pasuruan, 2021)
Insan Permata Hospital is a company engaged in the health sector, Insan Permata Hospital is a company that provides the best health services for the people in the city of South Tangerang with type C class and has followed accreditation from the Hospital Accreditation Commission (KARS) with achievements that have passed and get the main ranking or 4 stars. The process of selecting the best employee at the Insan Permata Hospital is based on direct observation in the assessment process carried out in paper format and this will certainly take a long time and the results are less objective, in selecting employees this is routinely carried out every semester, and the employee appraisal system is still subjective, of course this causes several problems including the accumulation of files, when data is needed, it takes a long time to look for it, data is slipped or lost and others. To overcome this, the authors try to provide a solution by comparing 2 methods, namely TOPSIS and SAW for selecting the best employees according to SDM requirements at Insan Permata Hospital, with 3 criteria including: Aspects of work based on Key Performance Indicators, Behavioral and Managerial Aspects . From the results of the comparisons made by the authors of the TOPSIS method, the solution needed compared to the SAW method, so that the problem of giving bonuses to the Permata Insan Hospital for the best employees can be resolved properly.Keywords: Comparison method, TOPSIS and SAW, Best Employees